Structure and functions of ErbB (HER) receptors - Falkiewicz, Bogdan; P. Bielawski, Krzysztof; Vogt, Ulf (Contemporary Oncology/Współczesna Onkologia, 1999)
The paper describes general characteristics, classification and structure of the tyrosine kinase receptor family ErbB ( HER ). They are encoded by two well-known proto-oncogenes erbB-1 ( HER1 , egfr) and erbB-2 ( HER2 , neu), as well as two genes of probably oncogenic function, namely erbB-3 ( HER3 ) and erbB-4 ( HER4 ). Receptors’ ligands, scheme of dimerisation, signal transduction and function were reviewed. Mechanisms leading to excessive activity of the receptor kinases (probably related to their oncogenic potential) were also denoted.